2018
DOI: 10.1002/imhj.21740
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers’ Use of Gesture and Speech in Service of Emotion Regulation During Distressing Routines

Abstract: Research on the intersections of young children's emerging communication skills and emotion regulation has increased, following recognition of the link between these skills as they emerge in toddlerhood and the long‐term impact of these skills on academic success. However, little is known about how toddlers use gesture and emerging language for emotion regulation. The current study describes toddlers’ use of both words and gestures in naturally occurring distressing routines in childcare (diaper change, separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Self-directed symbolic gestures have also been identified. Konishi et al (2018) found that children between 11 and 27 months used symbolic gestures during their routines in a childcare situation (diaper change and separation from parents) to self-regulate their emotions. Rodríguez (2009) referred to the case of Elisa, who was part of a longitudinal study.…”
Section: Rodríguezmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-directed symbolic gestures have also been identified. Konishi et al (2018) found that children between 11 and 27 months used symbolic gestures during their routines in a childcare situation (diaper change and separation from parents) to self-regulate their emotions. Rodríguez (2009) referred to the case of Elisa, who was part of a longitudinal study.…”
Section: Rodríguezmentioning
confidence: 99%
“…At the end of their first year, children start to communicate intentionally with others through gestures (Bates et al, 1979;Butterworth, 2003;Tomasello, 1999), which include pointing gestures, symbolic and ostensive gestures of giving and showing (Carpendale et al, 2021). By then, as shown above, they already produce self-directed gestures: private pointing gestures (Delgado et al, 2010), self-directed symbolic gestures (Konishi et al, 2018;Rodríguez, 2009) and private ostensive gestures (Dupertuis & Moro, 2016;Guevara et al, 2020;Moreno-Núñez et al, 2020;Moro et al, 2015). Furthermore, analysing self-directed gestures can shed a lot of light on how children resolve their difficulties.…”
Section: Construction and Development Of Executive Functioning: The C...mentioning
confidence: 99%
See 1 more Smart Citation